Розробка системи рейтингової оцінки нафтогазоперспективних локальних структур (на прикладі акваторій Чорного й Азовського морів) - Харченко, М.; Довжок, Т.; Маслюк, О.; Пономаренко, Л. (Геологія і геохімія горючих копалин, 2009)
На основі аналізу систем рейтингової оцінки структур визначено її головні принципи: співмірність підсумкової величини з перспективними ресурсами, можливість уточнення параметрів уже оцінених об’єктів, а також оцінки нових у тій самій системі. Для рейтингової оцінки перспективних структур української частини акваторій Чорного й Азовського морів було визначено 11 коефіцієнтів, об’єднаних у 3 групи: пошукові (успішності, зональної нафтогазоносності, типу пастки, амплітуди пастки, перспективності нафтогазоносних комплексів, якості структурних побудов, додаткових методів); розвідувальні (коефіцієнт ресурсів); економічні (віддаленості від комунікацій, глибини залягання перспективної товщі, глибини моря). Рейтингову оцінку підготовлених для глибокого буріння структур виконували двома етапами. Встановлено, що найбільш нафтогазоперспективними є структури Прикерченського шельфу Чорного моря, середньоперспективними – локальні структури Північно-Західного шельфу Чорного моря, найменш перспективними – локальні об’єкти Азовського моря. The basic principles of rating-based assessment of prospects of oil and gas content in structures, on the basis of well-known and well-designed systems of rating-based assessment analysis, are offered. These are: a commensuration of the results with prospective resources, a possibility of specifying estimated objects parameters, a new object assessment possibility in the same system. All the coefficients are divided into 3 groups: the exploration coefficients rate (a probability of hydrocarbon pools existence), the prospecting coefficients rate (the prospective resources volume), the economic coefficients rate (economic expediency of the structure geological survey). The full assessment is defined as multiplication of all the coefficients. The coefficients, defined for the rating-based assessment of prospects of local structures of the Ukrainian part of the Black Sea and Sea of Azov, are: a success coefficient, a zonal oil-and-gas-bearing coefficient, a trap type coefficient, a trap amplitude coefficient, an oil-and-gas-bearing complexes availability coefficient, a structural imaging quality coefficient, an adding methods coefficient, a coefficient of resources, a coefficient of a distance from communications, a perspective complex depth coefficient, a sea depth coefficient. The rating-based assessment of the prepared to the deep drilling structures in 2 stages is made. First only the exploration coefficients for all the prepared structures were considered. A value of resources has not an influence in this case on assessment of a reliability of the existence of proper hydrocarbon pools. By results of the first stage, 12 best objects are selected. A full assessment for these 12 objects was executed using prospect resources volume and economic coefficients. The most perspective structures, according to results of rating-based assessment, are local structures of the Kerch shelf of the Black Sea. The middle perspective of the oil-gaspresence is attached to local structures of the North-West shelf of the Black Sea. The prospects of the oil-gas-bearing of the Sea of Azov are less.